Romani tamburaši in Yugoslav black wave films: A turning point in visibility, recognition and agency - Baštić Јulijana; Forry Mark (Muzikologija)
Romani musicians in Serbia are masters of tambura ensemble playing - a multiethnic band string practice rooted in Central and Southeastern Europe. Through an analysis of Yugoslav Black Wave films and commercial recordings from 1965 to 1978, this study demonstrates how these musicians gained visibility and recognition both as individuals and as Roma within a specific socialist framework. To achieve this, they developed presentational skills in addition to participatory ones, effectively becoming bi-musical. This transition involved the commodification of their “Gypsyness”, which was ultimately leveraged to their advantage by both the musicians themselves and non-Romani cultural gatekeepers.